El juego simbólico en el desarrollo de la creatividad de los niños y niñas de 3 a 4 años de la Unidad Educativa Particular Nuevo Mundo, de la ciudad de Riobamba, periodo 2020-2021 - Procel Guamán, Evelyn Paola (2021)
The current investigation research was carried out on "The symbolic game in the development of the creativity of children from 3 to 4 years old of Unidad Educative Particular Nuevo Mundo, of Riobamba city, period 2020-2021", the aim is to identify the importance of working on creativity and how symbolic playing game influences this process. For the development of the proposal, qualitative research was carried out that allowed identifying which factors affect and how it intervenes in their creativity, which are the most common factors why teachers do not use the game as a teaching methodology in the classroom. This research was implemented on a bibliographical basis because the information was obtained from different sources such as books, magazines, articles, related to the research topic. The population consisted of five students and four teachers. In this study was used the observation sheet and a questionnaire as an instrument to gather the data of the current investigation. In the interpretation of the results obtained, the results obtained are that the children are at a level in which they do not develop their creativity through the use of symbolic games so the teachers do not use the playing game as a teaching methodology but rather as a fun, concluding that the symbolic game is a tool that allows them to work on the child's attention and develop their creativity.